Thermodynamic and whipping properties of milk fat in whipped cream: A study based on DSC and TD-NMR. (October 2019) - Wang, Yunna; Yuan, Dongdong; Li, Yang; Li, Meiling; Wang, Yuru; Li, Yan; Zhang, Liebing
Abstract: The correlation between thermodynamic and whipping properties of milk fat when used in recombined dairy cream (RDC) was investigated; thermodynamic behaviour of milk fat and the microstructure of RDC were analysed. Differential scanning calorimetry curves of anhydrous milk fats (AMFs) showed two peaks (7 °C and 15 °C), implying a difference in the crystallisation mechanisms. RDCs whipped at 7 °C demonstrated significantly higher cream overrun, firmness, and shorter optimum whipping time in comparison with these attributes at 15 °C. Additionally, RDC whipped at 7 °C generated bigger milk fat globules and was characterised by less flocculation and fewer broken air bubbles. Comparative analysis of the whipping properties at 7 °C and 4 °C revealed no significant differences. The results suggest that 7 °C is a more suitable temperature than 15 °C at which to whip RDC, and an ideal alternative temperature to that of 4 °C, for lower energy consumption.